Does the use of 50% oxygen at birth in preterm infants reduce lung injury?. Issue 5 (29th April 2005) - Harling, A E; Beresford, M W; Vince, G S; Bates, M; Yoxall, C W
Abstract : Background: Bronchopulmonary dysplasia is an inflammatory fibrotic condition produced as a consequence of injurious influences in the neonatal lung. Exposing the premature lung to high concentrations of oxygen is thought to play an important part in lung injury pathogenesis. Objective: To see if the amount of oxygen used during resuscitation at birth triggers events that lead to the subsequent lung injury and if a reduction in oxygen used leads to a reduction in lung injury. Method: The outcomes of newborn babies less than 31 weeks gestation who were resuscitated using either 50% or 100% oxygen were examined. Eight of the babies receiving 50% oxygen required an increase in their oxygen concentration. Evidence of pulmonary inflammation was determined by quantifying interleukin 6, 1β, and 10 and tumour necrosis factor α in bronchoalveolar lavage fluid by enzyme linked immunosorbent assay. Results: There were no significant differences in any of the cytokines studied in either of the groups. Death occurred in 5/26 (19%) babies who received 100% oxygen and 4/26 (15%) babies who received 50% oxygen. Survival without bronchopulmonary dysplasia at 36 weeks postmenstrual age occurred in 14/26 (54%) and 13/26 (50%). Conclusion: Reducing the oxygen to 50% at resuscitation did not influence either short or long term outcomes, but a small benefit could not be excluded. There was no increase in adverse clinical outcomes in babies who received 100% oxygen.